Accelerating Nitrate Electroreduction to Ammonia via Metal–Support Interactions in Ni-WS 2 Catalysts - Lv, Jiangnan; Yang, Qianwen; Liang, Tingting; Sun, Xiaoting; Rong, Wanting; Dai, Qiqi; Gao, Yizhi; Wang, Lanfang; Xu, Xiaohong; Liu, Yang (Journal of the American Chemical Society, 2025)
Electrocatalytic nitrate reduction reaction (NO RR) is a promising route for both treating NO -containing wastewater and enabling sustainable ammonia (NH ) synthesis. While two-dimensional (2D) transition metal dichalcogenides (TMDs) catalysts have been widely investigated as catalysts in various electrocatalytic reactions, their practical application in NO RR remains hindered by inherently sluggish kinetics and insufficient stability. Metal-support interaction (MSI), which enhances charge transfer and stabilizes catalytic sites, offers a compelling strategy to address these challenges. Herein, we design an MSI-driven Ni-WS catalyst via a two-step strategy. The Ni-WS catalyst demonstrates outstanding NO RR performance, achieving a Faradaic efficiency of 91.7% at -0.3 V with an NH yield rate of 23.3 mg h cm at -0.7 V . Significantly, the Ni-WS catalyst maintained an exceptional stability in a membrane electrode assembly (MEA), sustaining ≈32 mg h cm NH production over 100 h, surpassing most previously reported TMD-based catalysts. Density functional theory (DFT) calculations reveal that MSI between Ni metal and WS support induces interfacial charge redistribution, optimizes adsorption energy of key intermediates and lowers the energy barrier for the rate-determining step (*NH → *NH ). Furthermore, the Zn-NO battery assembled with Ni-WS cathode exhibits remarkable performance. This work advances a two-step synthesis strategy for high-performance NO RR electrocatalysts through targeted MSI modulation.